Morality and Politics in the Work of Michael Wyschogrod - Walzer, Michael (Modern theology, 2006)
Michael Wyschogrod claims that his arguments proceed from his biblical faith. But many of the (commendable) things that he has to say about politics and morality seem to derive from an autonomous ethics. I give five examples of arguments that cannot, in my reading of them, be drawn out of the relevant (but not definitive) biblical texts. Either the texts don't support the arguments at all, or they require interpretation, or some texts must be chosen above others if the arguments are to stand. Faith in the texts cannot by itself sustain the arguments that Wyschogrod wants to make.